Early disease detection expert system development: primary machining software applications and dependences - A. S. Serobabov; E. V. Chebanenko; L. A. Denisova; T. S. Krolevets (Омский научный вестник)
The article observes descriptive statistics tools for the biomedical information processing, clinical trials data on the nonalcoholic fatty liver disease (NAFLD). The primary machining software package structure which characterizes patienthood including the laboratory studies results, co-morbidity, patient’s physiological parameters is elaborated. The interconnections map of the patienthood diagnostics was retrieved, which enables to detect the dependences between the liver disease markers for the early disease detection expert system development.